Ultrasound‐guidance outperforms the palpation technique for peripheral venous catheterisation in anaesthetised toddlers: a randomised study. Issue 6 (9th May 2017) - Gopalasingam, N.; Obad, D. S.; Kristensen, B. S.; Lundgaard, P.; Veien, M.; Gjedsted, J.; Sloth, E.; Juhl‐Olsen, P.
Abstract : Background: Traditional palpation technique for peripheral venous catheter (PVC) placement can be challenging. We aimed to compare the Dynamic Needle Tip Positioning (DNTP) ultrasound technique with the palpation technique for PVC placement in anaesthetised toddlers undergoing elective, low‐risk procedures. Methods: The study was a randomised, controlled, crossover study. Five operators applied both techniques for PVC on 50 children < 4 years. The primary endpoint was first attempt success rate. The secondary endpoints were: (1) overall success rate, (2) number of skin perforations, (3) number of needle redirections, (4) number of catheters used, (5) total time, (6) needle manipulation time, (7) distance to the nearest flexion crease, (8) anatomical region of catheterisation, (9) size of the catheters and (10) the effects of visibility, and palpability of the veins. Results: The first attempt success rate and the overall success rate were significantly higher in the DNTP group (42/50 vs. 30/50, P = 0.029), (50/50 vs. 42/50, P = 0.008). Furthermore, a lower number of skin perforations (60 vs. 84, P = 0.013) and needle redirections (14 vs. 131, P < 0.001) and increased distance to the nearest flexion crease ( P < 0.001) were seen in the DNTP group. There were no significant differences in number of catheters used (60 vs. 75 P = 0.050) or total time ( P = 0.073), however, the needle manipulation time was longer in the DNTP group ( P = 0.011). The success rate decreased with less visible and palpable veins in the palpation group ( p = 0.006). Conclusion: Ultrasound‐guidance outperforms the traditional palpation technique for peripheral venous catheterisation in anaesthetised toddlers undergoing elective, low‐risk procedures.